Determinant factors of job quality in Europe - Crespo, N.; Simões, N.; Pinto, J. C. (Argumenta Oeconomica, 2017)
We analyze the determinants of job quality in Europe based on an individual level approach. Using data from the Fourth European Working Conditions Survey, covering 31 countries, we develop a multidimensional indicator of job quality including eleven dimensional indices, and confirm the influence of worker and company characteristics on the quality of jobs. Among worker characteristics, the factors that most strongly influence job quality are education and whether the worker is self-employed or a wage earner. The economic sector is the most important firm-related characteristic.